The Influence of Customer Relationship and Reference Groups on Customer Loyalty and Customer Satisfaction as Intervening Variables at Pt Bank Syariah - Tengku Syarifah; syaifuddin syaifuddin; Rusiadi Rusiadi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
PT Bank Syariah Indonesia has become one of the banking companies which currently has problems that have reduced public distrust. Therefore, this study will look for the influence of customer relationships and reference groups on customer loyalty and customer satisfaction as intervening variables at PT Bank Syariah. Collecting data in this study using quantitative methods. The results of the research show that Customer Relationship has a very large influence on Customer Loyalty. Likewise, Reference Groups also have a very significant influence on Customer Loyalty. So it can be said that Customer Relationship and Reference Groups are very important to be maintained by Pt. Islamic Bank.